Abeloff's clinical oncology - Abeloff, Martin D (Churchill Livingstone/Elsevier, 2008)
Carrying on the tradition established by its founding editor, the late Dr. Martin Abeloff, the 4th Edition of this respected reference synthesizes all of the latest oncology knowledge in one practical, clinically focused, easy-to-use volume. It incorporates basic science, pathology, diagnosis, management, outcomes, rehabilitation, and prevention - all in one convenient resource - equipping you to overcome your toughest clinical challenges. What\'s more, you can access the complete contents of this Expert Consult title online, and tap into its unparalleled guidance wherever and whenever you need it most!Equips you to select the most appropriate tests and imaging studies for diagnosing and staging each type of cancer, and manage your patients most effectively using all of the latest techniques and approaches.Explores all of the latest scientific discoveries\' implications for cancer diagnosis and management.Employs a multidisciplinary approach - with contributions from pathologists, radiation oncologists, medical oncologists, and surgical oncologists - for well-rounded perspectives on the problems you face.Offers a user-friendly layout with a consistent chapter format . summary boxes . a full-color design . and more than 1,445 illustrations (1,200 in full color), to make reference easy and efficient.Offers access to the book\'s complete contents online - fully searchable - from anyplace with an Internet connection.Presents discussions on cutting-edge new topics including nanotechnology, functional imaging, signal transduction inhibitors, hormone modulators, complications of transplantation, and much more. Includes an expanded color art program that highlights key points, illustrates relevant science and clinical problems, and enhances your understanding of complex concepts.Your purchase entitles you to access the web site until the next edition is published, or until the current edition is no longer offered for sale by Elsevier, whichever occurs first. If the next edition is published less than one year after your purchase, you will be entitled to online access for one year from your date of purchase. Elsevier reserves the right to offer a suitable replacement product (such as a downloadable or CD-ROM-based electronic version) should access to the web site be discontinued.
Keywords: lékařská onkologie; onkologie; Neoplasms; nádory; Medical Oncology